23 - EFFECT ON QUALITY OF LIFE IN FUNCTIONAL TRAINING AND BODYBUILDING PRACTITIONERS (Fiep Bulletin - online, 2023)
With the increase in concern with body image, it has been proportional with a relevant dimension through communication, propagating and valuing the aesthetic standard, so that the practice of physical activity has been helping for those who do not have the appropriate body, improving not only aesthetics but also health in general. The objective of this work was to evaluate the self-image of women who practice bodybuilding and Cross Trainer in the city of Patos-PB. This was a descriptive research with a quantitative approach to the data, the sample being composed of 20 bodybuilders and 20 Cross Trainers. The body image questionnaire (Body Shape Questionnaire - BSQ) were use and the statistical analysis was perform using Microsoft Office Excel 2007. It was faun that both bodybuilders and Cross Trainer practitioners showed higher percentages of absence of image distortion. In addition, as for the total points according to the questionnaire (BSQ) it was observed that bodybuilders had no image distortion, and Cross Trainer practitioners had slight image distortion. It is then conclude that both bodybuilders and Cross Trainer practitioners do not have high rates of distortion of their body image.
Keywords: Women. Body image. Bodybuilding. Cross Trainer